A Case of Delayed Fatal Hemobilia after Radiofrequency Ablation of Hepatocellular Carcinoma - Chung, Seung Kyu; Jun, Baek Gyu; Lee, Sae Hwan; Lee, Suck-Ho; Chung, Il-Kwun; Kim, Hong Soo; Park, Sang-Heum; Kim, Sun-Joo (Soonchunhyang medical science, 2012)
Radiofrequency ablation (RFA) has been accepted as a safe and effective treatment for unresectable hepatic tumors because of the advantages of a minimally invasive procedure and the local treatment effect. Although RFA can be performed safely in most patients,early and late complications related to mechanical or thermal damage may be observed at follow-up examination. Hemobilia is a very rare complication of RFA and most hemobilia is an immediate complication. However, delayed hemobilia is an even more rare complication after RFA and is known to be a fatal complication. We present a case of delayed fatal hemobilia after RFA for hepatocellular carcinoma. KCI Citation Count: 0